2011
DOI: 10.1039/c1cp22267h
|View full text |Cite
|
Sign up to set email alerts
|

Efficient crystallization induced emissive materials based on a simple push–pull molecular structure

Abstract: Solid state luminescent materials are the subject of ever growing interest both from a scientific and a technological point of view. Aggregation caused quenching (ACQ) processes however represent an obstacle to the development of most luminogens in the condensed phase. This is why particularly fascinating are those materials showing higher emission intensity in the solid state than in solution. Here we report on three 4-dialkylamino-2-benzylidene malonic acid dialkyl esters, very simple push-pull molecules, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 52 publications
2
54
1
Order By: Relevance
“…Another AIEgen with as imilar mechanism is 4-diethylamino-2-benzylidene malonic acid dimethyl ester (BIM), which contains as tyrene unit ( Figure 2). [59] Calculations combining TD-DFT,C ASSCF,a nd CASPT2 show that the molecule in methanol solutionr elaxes, initially,t oa ne xcited-state minimum with FClike structure, S 1 -EM. [44] However,a long the torsion coordinate of the styrene double bond there is af urther S 1 minimum, S 1 -CT,a nd aC I, S 1 /S 0 -CIb, at 908 and1 208 twist, respectively, where the excited state is aC Tstate from the benzene to the diesterm oiety ( Figure 4).…”
Section: Double Bond Torsion-dpdbfstyrene and Stilbene Derivativesmentioning
confidence: 99%
“…Another AIEgen with as imilar mechanism is 4-diethylamino-2-benzylidene malonic acid dimethyl ester (BIM), which contains as tyrene unit ( Figure 2). [59] Calculations combining TD-DFT,C ASSCF,a nd CASPT2 show that the molecule in methanol solutionr elaxes, initially,t oa ne xcited-state minimum with FClike structure, S 1 -EM. [44] However,a long the torsion coordinate of the styrene double bond there is af urther S 1 minimum, S 1 -CT,a nd aC I, S 1 /S 0 -CIb, at 908 and1 208 twist, respectively, where the excited state is aC Tstate from the benzene to the diesterm oiety ( Figure 4).…”
Section: Double Bond Torsion-dpdbfstyrene and Stilbene Derivativesmentioning
confidence: 99%
“…33 Assuming a = 5.36 Å, as estimated by computing the volume inside an isosurface of 0.001 e bohr À3 density, a fit from eqn (1) gives a value of m E À m G = 6.9 D (see Fig. 29,30 In the following we will focus our attention on the photophysical study of 1 dissolved in two solvents possessing different viscosities, acetonitrile (ACN, non-viscous) and polyethylene glycol (PEG, viscous), whose optical properties are reported in Fig. When the molecule is dissolved in viscous solvents, this simple relation does not hold, suggesting that additional effects, specifically related to solvent viscosity, have to be considered in the photoexcitation pathway.…”
Section: Photophysical Characterizationmentioning
confidence: 99%
“…11,29,30 In this paper, in order to shed more light on the excited state properties of push-pull systems and on the TICT mechanism, we report on the optical behavior of a new molecule, 1,1,1,5,5,5-hexafluoro-3-( p-dimethylaminophenyl)methylene-2,4-pentanedione, 1 (see Fig. 11,29,30 In this paper, in order to shed more light on the excited state properties of push-pull systems and on the TICT mechanism, we report on the optical behavior of a new molecule, 1,1,1,5,5,5-hexafluoro-3-( p-dimethylaminophenyl)methylene-2,4-pentanedione, 1 (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Such observations were consistent with the characteristics of CIE behavior and were commonly observed in AIE luminogens with blue to yellow emission. [47][48][49][50][51][52][53][54]56 For better understanding this phenomenon, the morphology evolution of aggregates formed in 50% aqueous solution was studied at different time intervals during storage. The scanning electron microscopic (SEM) image of nanoaggregates of the asprepared suspension revealed spherical morphology as a result of quick precipitation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is an effective way to increase the brightness of many AIEgens. [47][48][49][50][51][52][53][54][55] However, the preparation of crystals with sizes suitable for biological imaging is tricky. Liu et al reported a stress-induced seed assisted crystallization method, which can produce uniform AIE nanocrystals with sizes of around 100 nm.…”
Section: Introductionmentioning
confidence: 99%